The relationship between neuroticism, major depressive disorder and comorbid disorders in Chinese women. - Xia, J; He, Q; Li, Y; Xie, D; Zhu, S; Chen, J; Shen, Y; Zhang, N; Wei, Y; Chen, C; Shen, J; Zhang, Y; et al. (2011)
OBJECTIVE: The personality trait of neuroticism is a risk factor for major depressive disorder (MDD), but this relationship has not been demonstrated in clinical samples from Asia. METHODS: We examined a large-scale clinical study of Chinese Han women with recurrent major depression and community-acquired controls. RESULTS: Elevated levels of neuroticism increased the risk for lifetime MDD (with an odds ratio of 1.37 per SD), contributed to the comorbidity of MDD with anxiety disorders, and predicted the onset and severity of MDD. Our findings largely replicate those obtained in clinical populations in Europe and US but differ in two ways: we did not find a relationship between melancholia and neuroticism; we found lower mean scores for neuroticism (3.6 in our community control sample). LIMITATIONS: Our findings do not apply to MDD in community-acquired samples and may be limited to Han Chinese women. It is not possible to determine whether the association between neuroticism and MDD reflects a causal relationship. CONCLUSIONS: Neuroticism acts as a risk factor for MDD in Chinese women, as it does in the West and may particularly predispose to comorbidity with anxiety disorders. Cultural factors may have an important effect on its measurement.